Inter-institutional agreements for academic international cooperation: a discursive investigation of roles prescribed to higher education institutions - Salm, Adriane Marie (2005)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão. Programa de Pós-Graduação em Letras/Inglês e Literatura Correspondente